Understanding and Meaning of Da'wah from the Perspective of the Qur'an and Al-Hadith - Altruis Bizurai Chillyness; Moh. Ansori (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
ABSTRACT This study explores the definition and meaning of da'wah from the perspective of the Qur'an and Hadith, focusing on the fundamental principles and methods applied in the da'wah process. In the Qur'an, da'wah is explained through the call to invite to goodness (amar ma'ruf nahi munkar), which should not be done with force but rather with wisdom, good advice (mau'izhah hasanah), and polite debate (jidal bi allati hiya ahsan). The Hadith of the Prophet ﷺ reinforces that da'wah is the responsibility of every Muslim, even by conveying just one verse. The method of da'wah must be done with gentleness, in accordance with the principle that Allah loves gentleness in all matters. Furthermore, good character plays a central role in the success of da'wah. This study analyzes various verses of the Qur'an and Hadith to reveal the deep meaning of da'wah and its application in the life of Muslims, both in theory and practice. Keywords: Da'wah, Qur'an, Hadith, Wisdom, Mau'izhah Hasanah